Impacts of anthropogenic activities on vegetation cover changes in the Circum-Bohai-Sea region, China. Issue 25 (13th December 2022) - Jin, Kai; Jin, Yansong; Wang, Fei; Wang, Shaoxia
Abstract: Besides climate change, intensive anthropogenic activities affect vegetation cover variations, particularly in highly populated regions. Herein, we investigated the impacts of anthropogenic activities in the Circum-Bohai-Sea (CBS) region in China using correlation analysis between the normalized difference vegetation index (NDVI) and indicators related to urban development, agricultural practices, and afforestation efforts; multivariate linear regression and residual analyses were used to quantify how anthropogenic activities contribute to NDVI change. We found that the vegetation cover in most of the study area significantly increased from 1982 to 2015. In major cities, the decrease in vegetation cover was not as expected because of the opposing effects of rapid urbanization and greening. Afforestation and improved agricultural practices dominated the increase in vegetation cover in different regions. Anthropogenic activities accounted for 42% of the increase in vegetation cover in the CBS region. Therefore, to achieve regional sustainable development, the effects of human activities in highly populated area must be heeded.